PERUBAHAN MUTU BUAH TOMAT (Solanum lycopersicum) DENGAN PELAPISAN BERBASIS KITOSAN-BEESWAX DAN NANOPARTIKEL ZnO SELAMA PENYIMPANAN - Setyadi Gumaran; Friska Tania Hutabarat; Hadi Yusuf Faturochman; Edy Tya Gullit Duta Pamungkas (Partner, 2023)
Tomatoes are an agricultural commodity that will experience an increase in respiration rate and ethylene production after harvesting. Ethylene in fruits will accelerate ripening, resulting in a shorter shelf life for the fruit. Chitosan-beeswax and NP-ZnO can retain the soluble solids of the fruit, inhibit respiration, and exhibit antibacterial properties, making them suitable as a coating material. This study aims to investigate the effect of chitosan-beeswax coating with the addition of ZnO nanoparticles on the quality changes of tomato fruits during storage. Coating tomato fruits with the spray method using 3% chitosan-beeswax and 3% NP-ZnO addition resulted in a weight loss value of 4.98% on the 10th day, while the control group had the highest weight loss value at 8.57%. The hardness of the control tomato fruits had the highest value at 7.72 N, whereas the 3% chitosan-beeswax treatment with 3% NP-ZnO addition exhibited a hardness of 9.64 N on the 10th day of storage. The research findings indicate that the addition of chitosan-beeswax and NP-ZnO can maintain the hardness and reduce weight loss in tomato fruits. Key Words: Coating, Chitosan, Beeswax, NP-ZnO, Storage